Early Childhood Respiratory Morbidity and Health Services Utilization in Children Born Preterm or Small and Large for Gestational Age - Jesus Serrano-Lomelin; Radha Chari; Anne Hicks; David Johnson; Susan Crawford; Jeff Bakal; Alvaro Osornio-Vargas; Maria Ospina (International Journal of Population Data Science, 2018)
Introduction Alterations in duration of gestation and fetal growth such as preterm birth (PTB) or small and large for gestational age (SGA, LGA) have long-term consequences on respiratory health. The risk of health services use for respiratory conditions in infants born PTB, SGA or LGA in Canada needs to be evaluated.